Safety and efficacy of daclatasvir and asunaprevir in hepatitis C virus‐infected patients with renal impairment - Suda, Goki; Nagasaka, Atsushi; Yamamoto, Yoshiya; Furuya, Ken; Kumagai, Kenichi; Kudo, Mineo; Terashita, Katsumi; Kobayashi, Tomoe; Tsunematsu, Izumi; Yoshida, Junichi; Meguro, Takashi; Kimura, Megumi; et al. (Hepatology research, 2017)
Aim Hepatitis C virus (HCV) infection is a risk factor for end‐stage renal disease, renal graft failure, and hemodialysis patient mortality. However, the efficacy of direct‐acting antiviral therapy for HCV‐infected patients with renal impairment is unclear. Additionally, the promising NS5B inhibitor sofosbuvir has not been recommended for patients with severe renal impairment. In this prospective, multicenter study, we evaluated the efficacy and safety of daclatasvir and asunaprevir combination therapy, with a focus on patients with renal impairment. Methods The study included 322 genotype 1 HCV‐infected patients who received daclatasvir and asunaprevir combination therapy. The safety and sustained virological response was examined at 12 weeks after the end of treatment and safety was evaluated according to renal function. Results Of 322 patients, 5% (16/322) and 2.5% (8/322) had chronic kidney disease stage G3b (estimated glomerular filtration rate [eGFR], 30–44 mL/min/1.73 m2) and stage G4/5 (eGFR, 15–29/<15 mL/min/1.73 m2), respectively. Baseline presence of the NS5A resistance‐associated variant, previous simeprevir treatment, and HCV RNA titers, which were predictors of a sustained viral response, were similar between patients with eGFR <45 mL/min/1.73 m2 and eGFR >45 mL/min/1.73 m2. Notably, the 12‐week sustained viral response rate was comparable in patients with eGFR <45 mL/min/1.73 m2 (100%, 24/24) and those with eGFR >45 mL/min/1.73 m2 (88.9%, 265/298; P = 0.07). Treatment discontinuation rates and adverse events, including alanine aminotransferase elevation, anemia, and renal disorders, were similar between the two groups. Conclusion Daclatasvir and asunaprevir combination therapy for patients with renal dysfunction was highly effective and safe.